Statistical models for estimating the distribution function of alcohol consumption : a parametric approach - Alanko, Timo (Alkoholitutkimussäätiön julkaisuja, ISSN 0356-2654, 1997)
Abstract (s. iv).
Keywords: ennusteet; tilastomenetelmät; alkoholijuomat : kulutus; alkoholinkäyttö; kulutus